PENGARUH VOLUME KENDARAAN TERHADAP TINGKAT KERUSAKAN JALAN PADA PERKERASAN LENTUR (Study Kasus Ruas Jalan Keongsari - Blebak STA 0+000 – 1+300 & Karanggondang – Mpurancak STA 0+000 – 1+300) - Rizki, Muhammad Efendi; Saputro, ST., MT., Yayan Adi; Rochmanto, Decky; Faqih, Nasyiin; Roehman, Fatchur (Jurnal Konstruksi dan Infrastruktur : Teknik Sipil dan Perencanaan, 2024)
The number of two-, four- or four-wheeled motorized vehicles is increasing in Jepara Regency. With the increasing number of vehicles, it is estimated that roads will experience damage in a relatively short time. The aim of this research is to determine the effect of vehicle traffic on the level of road damage and the relationship between vehicle traffic and the level of road asphalt damage. The method used to determine the value of road damage is the PCI method and the level of road damage uses the non-linear multiple regression method. This research was carried out on two roads, namely Jalan Keongsari – Blebak and Jalan Karanggondang – Mpurancak. It is known that the average damage that occurs on the Keongsari - Blebak road section is 39.29 (BAD) including the Overlay maintenance type, while the Karanggondang - Mpurancak road section has an average damage value of 67.14 (GOOD) if routine maintenance is carried out. pen type. The results of measuring the thickness of the additional layer (overlay) using the road composition analysis method on the Keongsari – Blebak road section obtained an additional layer thickness of 5 cm using LAPEN material. Meanwhile, the results of the relationship between vehicle traffic and road damage show that traffic (pcu/hour) and time (hours) have a large influence on road damage. This is shown by the results of determining the R2 coefficient of 86%. Keyword: Damage, Road, Flexure, Overlay, Highway.